The Role Of Digital Tools in Teaching Science: A Comparative Study Of Traditional and Technology-Enhanced Methods - Irna Ardhita; Imam Khanafi (International Journal of Mathematics and Science Education, 2024)
This research investigates the role of digital tools in the teaching of science, comparing traditional instructional methods with those enhanced by technology. A series of classroom interventions were implemented in secondary schools, utilizing digital simulations and interactive platforms. The results indicate that technology-enhanced methods improved student engagement, understanding of complex scientific concepts, and academic performance. The paper highlights the potential of digital tools to transform science education and recommends strategies for their effective integration in the classroom.